Hawksbill x loggerhead sea turtle hybrids at Bahia, Brazil: where do their offspring go? - Proietti,Maira C; Reisser,Julia; Marins,Luis F.; Marcovaldi,Maria A.; Soares,Luciano S; Monteiro,Danielle; Wijeratne,Sarath E.M.; Pattiaratchi,Charitha; Secchi,Eduardo R. (PeerJ PrePrints, 2013)
Hybridization between hawksbill (Eretmochelys imbricata) and loggerhead (Caretta caretta) breeding groups is unusually common in Bahia state, Brazil. Such hybridization is possible because hawksbill and loggerhead nesting activities overlap temporally and spatially along the coast of this state. Nevertheless, the destinations of their offspring are not yet known. This study is the first to identify immature hawksbill x loggerhead hybrids (n = 4) from this rookery by analyzing the mitochondrial DNA (mtDNA) of 157 immature turtles morphologically identified as hawksbills. We also compare for the first time modeled dispersal patterns of hawksbill, loggerhead, and hybrid offspring considering hatching season and oceanic phase duration of turtles. Particle movements varied according to season, with a higher proportion of particles dispersing southwards throughout loggerhead and hybrid hatching seasons, and northwards during hawksbill season. Hybrids from Bahia were not present in important hawksbill feeding grounds of Brazil, being detected only at areas more common for loggerheads. The genetic and oceanographic findings of this work indicate that these immature hybrids, which are morphologically similar to hawksbills, could be adopting behavioral traits typical of loggerheads, such as feeding in temperate waters of the western South Atlantic. Understanding the distribution, ecology, and migrations of these hybrids is essential for the development of adequate conservation and management plans.
Keywords: hybridization; Western South Atlantic; mitochondrial DNA; juvenile sea turtles; satellite-tracked buoys; particle tracking; dispersal models; juvenile sea turtles; hybridization; Western South Atlantic; particle tracking; mitochondrial DNA; dispersal models